Social entrepreneurship and inclusive growth: Attributes, perceptions and roles of business incubators and intermediaries in Malaysia - Baskaran, A.; Tang, M.; Thiruchelvam, K.; Shahabudin, S.M.; Chan, T.S.Y. (2017)
Social enterprises are considered to be at the heart of inclusive growth due to their emphasis on people and social cohesion that help effect social and economic transformation. Malaysia's New Economic Model (NEM) set out high income, sustainability and inclusiveness, as the foundation for transformation towards an advanced nation by 2020. In the Tenth Malaysia Plan (2011-2015), 2 out of 10 objectives are 011 achieving inclusive growth. In this context, this paper explores the eco-system for social enterprises in Malaysia, raising the following research questions: J. What are the attributes (features) of business incubators and intermediaries operating in the social enterprise sector in Malaysia; 2. What are the perceptions of business incubators and intermediaries about various aspects of social enterprise ecosystem in Malaysia? 3. What is the role of business incubators and other intermediaries in fostering social entrepreneurship in Malaysia in general and meeting the inclusive growth objective of the country in particular? The study employs qualitative approach and primary data gathered through interviews of 6 business incubators and intermediaries, and 20 social enterprises. The study found that the current social enterprise ecosystem is weak and still emerging and yet to take a concrete shape. The absence 0/ legal status /01' social enterprise is the single most important obstacle in unlocking the potential growth 0/ social enterprises. 1t is seriouslv constraining the private sector participation such as coupling of corporate social responsibility (CSR) related funding with the development of social businesses. The study suggests that the government initiate policy measures to give legal status to social enterprise in the country in order to develop the ecosystem and facilitate greater participation of the private sector.